Thermo–Elastic Stresses and Deformation Analysis of FG Rotating Hollow Spherical Body - Lakshman Sondhi; Rakesh Sahu; Shubhankar Bhowmick; Amit Thawait (Mechanics of Advanced Composite Structures)
In this paper, a generalized solution for 1-D steady-state thermo-mechanical analysis of the FG rotating hollow spherical body is presented. Deformation and stresses are calculated for a spherical body subjected to rotation, gravitation force, and uniform heat generation. Temperature distribution with uniform heat generation to the spherical body is assumed to vary along the radius. General thermal and mechanical boundary conditions at the inner surface and outer surfaces of the hollow spherical body are applied. Material properties are assumed as a power function of the radius with grading indices ranging from -2 to 3. Governing differential equation for the FG spherical body is developed and solved analytically. The obtained results are verified with benchmark results and are found to be in very good agreement. The result shows that deformation and stresses in the FG body are less compared to the homogeneous material body and the same is reported to decrease with increasing value of the grading parameter.